PELAKSANAAN BELAJAR MENGAJI DI MASJID MIFTAHUL JANNAH BUKIT PERMAI KECAMATAN BANGKINANG KOTA - Ardhi, Fitra; Irja, Desti; ', Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the implementation of learning to learn in the mosque Miftahul Jannah Bukit Permai District Bangkinang City. The formulation of the problem in this research is how the implementation of studying in mosque miftahul jannah bukit permai kecamatan bangkinang city? After this research is conducted, it is expected to give benefit to the students to increase student's learning interest and the teacher can implement the study program well to increase people's knowledge about matters relating to the implementation of study in mosque miftahul jannah hillside district of urban bangkinang. This research is phenomenology with qualitative approach, in an effort to take the data of research, hence researcher use interview technique, observation and documentation. As a reference to conduct research in the field, researchers prepare a grid in the form of questions to be used as an interview of respondents. After data collected, data analysis techniques, including data reduction, data presentation, and data verification to obtain the level of trust (validity) of the research findings are carried out technique (1) credibility test through extension of observation, increasing persistence, triangulation, and using reference materials 2) testing of transferability (3) dependability test (4) komfirmability testing conducted by editing process and research results. This study is about the implementation of study in the mosque Miftahul Jannah Bukit Permai District Bangkinang City viewed from the orientation activities, teaching and learning activities, determining the level of mastery of materials, Inform or report back the level of mastery of each student, Checking the effectiveness of the overall program.Keywords: Learning Learning Implementation